1996
DOI: 10.1046/j.1365-2141.1996.d01-1840.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Lleida: a new α2‐globin variant (12 bp deletion) with mild thalassaemic phenotype

Abstract: Molecular studies of alpha-thalassaemias have revealed defects at different steps in the process of alpha-gene expression. It is not surprising, therefore, that in some cases a single mutation or small deletion can result in a structurally abnormal haemoglobin that produces the alpha-thalassaemia phenotype. In this report we describe a new unstable alpha-globin variant, Hb Lleida, in a Spanish patient with alpha-thalassaemia trait. The mutation was detected by single-strand conformation polymorphism in the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Since none of the known -thalassaemia determinants was found, the complete 1 and 2 -globin genes were amplified by polymerase chain reaction (PCR) using previously described primers (Dodé et al, 1990). An aliquot of these PCR products was used as a template to amplify the exon and intron boundaries into three different fragments for each gene, using a combination of specific primers (Ayala et al, 1996b). Then, these fragments were submitted to non-radioactive SSCP analysis as described previously (Ayala et al, 1996b).…”
Section: Single Strand Conformation Polymorphism (Sscp) Analysis and mentioning
confidence: 99%
See 1 more Smart Citation
“…Since none of the known -thalassaemia determinants was found, the complete 1 and 2 -globin genes were amplified by polymerase chain reaction (PCR) using previously described primers (Dodé et al, 1990). An aliquot of these PCR products was used as a template to amplify the exon and intron boundaries into three different fragments for each gene, using a combination of specific primers (Ayala et al, 1996b). Then, these fragments were submitted to non-radioactive SSCP analysis as described previously (Ayala et al, 1996b).…”
Section: Single Strand Conformation Polymorphism (Sscp) Analysis and mentioning
confidence: 99%
“…An aliquot of these PCR products was used as a template to amplify the exon and intron boundaries into three different fragments for each gene, using a combination of specific primers (Ayala et al, 1996b). Then, these fragments were submitted to non-radioactive SSCP analysis as described previously (Ayala et al, 1996b). The region of the -globin gene showing an abnormal mobility by SSCP was reamplified by using specific flanking primers, one of which was biotinylated at the 5' end.…”
Section: Single Strand Conformation Polymorphism (Sscp) Analysis and mentioning
confidence: 99%
“…When the above screen was negative, the entire a 1 -and a 2 -globin genes were submitted to non-radioactive PCR-SSCP analysis as described previously (Ayala et al, 1996b), for rapid detection of point mutations, short deletions or insertions. Fragments showing an abnormal SSCP band pattern with a mobility shift or the presence of extra bands, indicate the possible existence of some gene abnormality.…”
Section: Methodsmentioning
confidence: 99%
“…This new mutation reduces the aglobin output and leads to the mild a-thalassaemic phenotype in the affected subject. In addition to the intrinsic interest of this case, our study demonstrated that the nonradioactive single-strand conformation polymorphism (SSCP) analysis, devised in our laboratory during the last two years (Ayala et al, 1996b), is a powerful tool for the routine detection of specific mutations in a-thal.…”
mentioning
confidence: 99%
“…α-genes: Ayala et al (5), used the singlestrand conformation polymorphism (SSCP) technique described by Orita et al (6), and Harteveld et al (7) used SSCP in combination with denaturating gradient gel electrophoresis (DGGE) (8). These two methods, however, present some disadvantages because the former is a radioactive SSCP and the latter combines two techniques and two different types of equipment, with the DGGE Figure 1.…”
mentioning
confidence: 99%